Efeito da restrição proteica gestacional sobre parâmetros morfométricos e metabólicos e sobre o comportamento alimentar na prole de camundongos - Silva, Luana Cristina de Almeida [UNIFESP] (2016)
Objective: The objective of this study was to analyze the metabolic and behavioral effects of fetal growth restriction (IUGR) caused by the deficiency of protein during intrauterine life before and after exposure to high-fat diet. Method: After protein restriction (5g protein / 100 g diet, HP diet) in the maternal diet offspring, it was compared with offspring of mothers receiving normal protein diet (20 g protein / 100 g diet, NP diet). After birth, all offspring were suckled by progenitors fed NP diet and, there was adoption of all litters by progenitors fed NP diet. In postnatal day (PND) 28 a total of 51 offspring were distributed into two groups according to the maternal diet, namely: control group (CT, HP maternal diet) and restriction group (RT, NP maternal diet). The offspring were accompanied for 2 months receiving NP diet and, after this period all of them were fed with a high-fat diet with high concentration of saturated fat (31g saturated fat, 100g diet, HL) for about 5 weeks. The body weights of the offspring were accompanied weekly from birth to the 1st month of life and, monthly from 1st month until euthanasia. The naso-anal length was measured in PND30 and PND60. Blood samples were collected in PND30, PND60 and PND90 to assess blood concentrations of glucose, total cholesterol and triglycerides in whole blood and plasma concentrations of insulin and leptin. The animals were subjected to behavioral tests: Novelty suppressed-feeding test and open field. After behavioral assessments, the animals were euthanized by decapitation and had blood, fat, liver, kidney and muscle collected. Data is presented as mean ± standard deviation. Results and conclusions: IUGR decreased the birth weight of offspring and this effect can be observed at other times throughout the study; in males, this restriction reduced the naso-anal growth and altered muscle mass and the proportion of fat after high fat diet consumption. After spending the period stipulated feeding only at HL diet, restricted animals showed elevated plasma insulin. Males and females RT group showed increased locomotor activity, restricted females also had fewer episodes of self-cleaning during behavioral 95 testing and showed a higher consumption of HL diet over time in relation to the females CT group. With these data, we can conclude that the deficiency in maternal nutrition delayed intrauterine growth, and this effect can interfere in the post-natal development, affecting morphometric parameters before and after consumption of a HL diet. After passing through metabolic challenge exposure (HL diet), restricted animals showed elevated plasma insulin, demonstrating that IUGR may influence metabolic signaling involved in energy homeostasis promoted by a nutritional imbalance.